1957
DOI: 10.1104/pp.32.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Physiology of Tomato Fruits. II. Ethylene Production at 20° C as Related to Respiration, Ripening, and Date of Harvest

Abstract: This study establishes the rate a1-nd pattern of ethylene production by ripening tomato fruits (Lycopersicum esculen tum MIiller) and relates this to respiration (carbon dioxide evolution) and the stage of ripeness as shown by red color development. The influence of the harvest date has been investigated, since the changing environmental conditions encountered during a harvest season might influence the ethylene producing ability of the fruit and hence its ability to ripen properly late in the season. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1960
1960
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The development of the red color over the complete ripening sequence is shown in Figure 1A using fruits selected according to the color description of Workman and Pratt (10). Similar changes were observed with harvested fruits ripening under the conditions of the pericarp disk experiments (Fig.…”
Section: Resultssupporting
confidence: 57%
“…The development of the red color over the complete ripening sequence is shown in Figure 1A using fruits selected according to the color description of Workman and Pratt (10). Similar changes were observed with harvested fruits ripening under the conditions of the pericarp disk experiments (Fig.…”
Section: Resultssupporting
confidence: 57%
“…During the early stages of tomato fruit development, for example, the immature green fruit produces little ethylene. One of the earliest observable events in tomato ripening is a sharp increase in the rate of ethylene formation (4). A number of subsequent ripening-related processes are controlled by ethylene (5).…”
mentioning
confidence: 99%
“…Since ripening has been more thoroughly characterized in tomato pericarp than in any other fruit or tissue (4,14), a detailed comparison is possible. Previous studies have shown that, during normal ripening ofpericarp in intact tomato fruit, tissue color changes from green through orange to red (10,18), ethylene biosynthesis and respiration undergo a climacteric rise (35), tissues decrease in firmness (21), extractable activities of specific hydrolytic enzymes increase (7,17,19,28,34), and various fractions of the cell wall change in composition (15,16). In this article, these characteristics of ripening in whole fruit, as described here or by others, are compared with similar processes in excised pericarp discs.…”
mentioning
confidence: 99%
“…These processes are induced and coordinated, in part, by the biosynthesis and diffusion of ethylene (5,25,26,35), by local differences and changes in sensitivity to ethylene (5,25), and, perhaps, by other regulatory signals (6).…”
mentioning
confidence: 99%